The Historical Emergence of Quantity Theory: Comments - Hamilton, Earl J. (Quarterly Journal of Economics, 1935)
Journal Article Comments Get access Earl J. Hamilton Earl J. Hamilton Duke University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 50, Issue 1, November 1935, Pages 185–192, https://doi.org/10.2307/1882349 Published: 01 November 1935